2021
DOI: 10.3390/ph14090935
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolomic Approach Reveals the Alteration in Human Serum and Cerebrospinal Fluid Composition in Parkinson’s Disease Patients

Abstract: Parkinson’s disease (PD) is a major public health problem. Since currently there are no reliable diagnostic tools to reveal the early steps of PD, new methods should be developed, including those searching the variations in human metabolome. Alterations in human metabolites could help to establish an earlier and more accurate diagnosis. The presented research shows a targeted metabolomics study of both of the serum and CSF from PD patients, atypical parkinsonian disorders (APDs) patients, and the control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 75 publications
1
27
1
Order By: Relevance
“…Proline is involved in aging and neurodegeneration [ 300 , 301 ]. In this regard, a recent study found high concentration levels of ornithine—the precursor of proline—in the sera of patients with PD [ 302 ], confirming results obtained by Çelik et al [ 303 ]. Ornithine accumulation is associated with hyperosmolarity in different regions of the brain via urea cycle flux [ 303 ].…”
Section: Metabolic Alterations In Ad and Pd Brainssupporting
confidence: 81%
See 1 more Smart Citation
“…Proline is involved in aging and neurodegeneration [ 300 , 301 ]. In this regard, a recent study found high concentration levels of ornithine—the precursor of proline—in the sera of patients with PD [ 302 ], confirming results obtained by Çelik et al [ 303 ]. Ornithine accumulation is associated with hyperosmolarity in different regions of the brain via urea cycle flux [ 303 ].…”
Section: Metabolic Alterations In Ad and Pd Brainssupporting
confidence: 81%
“…Additionally, ornithine accumulation leads to higher proline levels, which could induce collagen biosynthesis, leading to a shift in the immune system towards a program of wound healing [ 303 ]. Increased levels of trans-4-hydroxyproline were found in the CSF and sera of patients with PD—possibly partially caused by the intensified degradation of collagen [ 302 , 304 ].…”
Section: Metabolic Alterations In Ad and Pd Brainsmentioning
confidence: 99%
“…Metabolomics has attracted attention in recent years, revealing multiple novel metabolic pathways linked to the pathogenesis of PD. Several studies demonstrated altered metabolic profiles in PD, PD subgroups, APS and other neurological conditions [ 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. By utilizing machine learning algorithms, 14 CSF metabolites were identified that enabled distinguishing early PD from controls with high accuracy [ 104 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Moreover, a link between altered metabolic profiles and the tricarboxylic acid cycle has been observed, which are implicated in mitochondrial dysfunction and increased oxidative stress [ 106 ]. By using liquid chromatography–tandem mass spectrometry, a recently published study detected increased CSF levels of intermediates of the proline metabolic pathway in PD and APS subjects that could discriminate them from controls but not among parkinsonian syndromes [ 97 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Besides these, many altered metabolites in the CSF of patients with PD compared with controls have been reported. The levels of trans-4-hydroxyproline [62], α-N-phenylacetyl-L-glutamine [63], (+)-gammahydroxy-L-homoarginine [63], p-cresol sulfate [64], decanoic acid [64], 10-hydroxydecanoic acid [64], dihomo-γ-linolenic acid [64], and diacylglycerol [65] have been shown to be increased, while those of betaine [63], dimethylglycine [63], α-aminobutyric acid [66], ornithine [66], lysine [66], and histidine [66] have been shown to be decreased.…”
Section: Metabolomic Differences In the Csf In Pd And Msamentioning
confidence: 99%